2021
DOI: 10.1038/s41598-021-99337-2
|View full text |Cite
|
Sign up to set email alerts
|

Demography of a Eurasian lynx (Lynx lynx) population within a strictly protected area in Central Europe

Abstract: Large carnivores promote crucial ecosystem processes but are increasingly threatened by human persecution and habitat destruction. Successful conservation of this guild requires information on long-term population dynamics obtained through demographic surveys. We used camera traps to monitor Eurasian lynx between 2009 and 2018 in a strictly protected area in the Bohemian Forest Ecosystem, located in the core of the distribution of the Bohemian–Bavarian–Austrian lynx population. Thereby, we estimated sex-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 57 publications
(89 reference statements)
0
13
0
Order By: Relevance
“…2). Here, the terminal node with 20 surveys from nine studies (Hearn et al 2016, Ramesh et al 2017, Wang et al 2017, Balme et al 2019, Lamichhane et al 2019, Tempa et al 2019, Kittle et al 2021, Palmero et al 2021, Searle et al 2021) with the number of individuals >20 had the highest precision (mean CV = 0.16; SD = 0.06). The lowest precision results (mean CV = 0.49; SD = 0.17) were obtained in the first group and a terminal node with 19 surveys from 10 studies (Ramesh et al 2012, Sunarto et al 2013, Singh et al 2014, Thornton & Pekins 2015, Ramesh et al 2017, Hearn et al 2019, Mohamed et al 2021, Naing et al 2019, Noor et al 2020, Duľa et al 2021) with low numbers of individuals (≤5) and recaptures (≤22).…”
Section: Resultsmentioning
confidence: 96%
“…2). Here, the terminal node with 20 surveys from nine studies (Hearn et al 2016, Ramesh et al 2017, Wang et al 2017, Balme et al 2019, Lamichhane et al 2019, Tempa et al 2019, Kittle et al 2021, Palmero et al 2021, Searle et al 2021) with the number of individuals >20 had the highest precision (mean CV = 0.16; SD = 0.06). The lowest precision results (mean CV = 0.49; SD = 0.17) were obtained in the first group and a terminal node with 19 surveys from 10 studies (Ramesh et al 2012, Sunarto et al 2013, Singh et al 2014, Thornton & Pekins 2015, Ramesh et al 2017, Hearn et al 2019, Mohamed et al 2021, Naing et al 2019, Noor et al 2020, Duľa et al 2021) with low numbers of individuals (≤5) and recaptures (≤22).…”
Section: Resultsmentioning
confidence: 96%
“…death from a natural cause, were slightly higher. Likewise, in a strictly protected area in the Bohemian Forest, lynx were not found to be strongly affected by human-related mortality 34 . By contrast, a study in the Swiss Alps and the Jura Mountains (Switzerland) showed that natural causes accounted for 44.9% of all established causes of death in this region and that infectious diseases accounted for 26.5% of them.…”
Section: Discussionmentioning
confidence: 87%
“…At the same time, it is estimated that under natural conditions, only 24% of lynx lived for three years in the Białowieża Forest (Poland) 33 . A study carried out in the Bohemian Forest, on the Czech-German border, indicated that individuals up to 4 years of age made up 64% of the entire population and that the mean generation time for resident reproducing females was 2.64 years 34 . Meanwhile, the probability of reaching the age of 2.5 years for lynx reintroduced to north-western Poland was 51.1%.…”
Section: Discussionmentioning
confidence: 99%
“…The dynamics of lynx in the Ukrainian Carpathians and Polissya according to official summary data was stable without significant fluctuations during 2009-2019. The Eurasian lynx is a species sensitive to globalization, its number and distribution are negatively affected by disturbance, loss of habitats and food base (Palmero et al, 2021). Poaching also remains the main reason for the decline in the number of Eurasian lynx all over Europe (Červený et al, 2019).…”
Section: Discussionmentioning
confidence: 99%